(untitled) (Revista Internacional de Folkcomunicação, 2024)
The work aims to understand popular culture through the bias of its televisualidade through the analysis of the documentary series Sou cultura popular (2023), produced in a partnership between UERN TV and the channel Futura and distributed by Globoplay. The theoretical contribution is based on streaming studies (Bahia et al., 2022), reflections about televisions (Rocha, 2019) and folkcommunicational research (Trigueiro, 2019 and 2008; Macedo; Furtado, 2018 and Marques de Melo, 2008). Methodologically, this summary applied the Convergent Television Analysis (ATC) proposed by Becker (2019), expanding the analytical scheme of the Becker Television Analysis (2012, 2016b, 2019), to understand how the documentary series is included in the scope of television services. From a corpus of 4 episodes observed in the months of October and November 2023, supported by the results achieved, this research points to the presence of players and craftsmen in audiovisual production, that is disseminated in digital platforms such as streaming, Youtube and applications. Another relevant point is the presence of characteristics of the northeast region in the narrative with the accent of the interviewees, because in general the northeastern accent is represented by actors and actresses in audiovisual productions of Globo, Thus the series becomes an authentic channel of northeastern culture.